TAFSSA District Agrifood Systems Assessment in India 2023: Local Market and Retail Census - International Rice Research Institute; International Food Policy Research Institute (International Food Policy Research Institute, 2024)
TAFSSA (Transforming Agrifood Systems in South Asia) is a CGIAR Regional Integrated Initiative aimed at advancing equitable access to sustainable healthy diets, enhancing farmers' livelihoods and resilience, and conserving natural resources such as land, air, and water across South Asia. The TAFSSA district agrifood systems assessment seeks to establish a robust, accessible, and integrated evidence base that connects farm production, market access, dietary patterns, climate risk responses, and natural resource management, with gender considerations integrated throughout. The assessment focuses on rural areas in Bangladesh, India, and Nepal, utilizing a district-level, multi-year approach. In December 2022–January 2023, data collection was conducted in the Nalanda district of Bihar, India. A census was carried out in 50 villages selected using probability proportional to the number of households in each village. The census included all formal and informal multi-vendor markets offering a variety of food products, as well as retail food shops in the selected villages. The types of multi-vendor markets covered included village markets, weekly village markets, roadside/street markets, and wholesale markets (mandis). Retail shops included local grocery stores, vegetable/fruit shops (green grocers), and specialized shops selling meat, eggs, fish, or dairy products. The census employed pretested, structured questionnaires to gather data. Information collected included market density, vendor details, opening hours and days, products sold, infrastructure and facilities in shops, waste disposal methods, and GPS coordinates of the retail shops and markets.